Institutions and investment : the political basis of industrialization in Mexico before 1911 - Beatty, Edward (Social science history., 2001)
The author offers the first systematic explanation of why private investment came to Mexican domestic industry in an era when we would expect investors to prefer export-oriented activities, and when imported manufactures held every advantage in the domestic market. He shows that the government of Porfirio Di; az encouraged the development of a domestic industrial sector through a planned and carefully administered set of laws and policies, including commercial policy (import tariffs), intellectual property law (patents), and the New Industries program. This study also offers a case study of rapid institutional change in the context of a relatively backward and transitional economy. Within a theoretical context, it argues that institutions play a crucial role in shaping investment behavior, but that understanding this relationship requires careful attention to the structure of policy and to the broader economic and historical context.--Provided by publisher.